2022
DOI: 10.1186/s13099-022-00504-1
|View full text |Cite
|
Sign up to set email alerts
|

Rapid screening for antigenic characterization of GII.17 norovirus strains with variations in capsid gene

Abstract: The emergence of the novel GII.17 Kawasaki 2014 norovirus variant raising the interest of the public, has replaced GII.4 as the predominant cause of noroviruses outbreaks in East Asia during 2014–2015. Antigenic variation of the capsid protein is considered as one of the key mechanisms of norovirus evolution. In this study, we screened a panel of GII.17 mutants. First, we produced norovirus P proteins using cell-free protein synthesis (CFPS) system, comparing the results to pure proteins expressed in a cell-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…This study further analysed the VP1 protein, and the amino acid variation comparison revealed that it was greater in the P2 subdomain than in the P1 subdomain and S domain. Further, the threedimensional visualisation model of the VP1 protein also verified that there was a correlation between the alteration of the P2 subdomain and the alteration of the NoV genotype, which verified the outcomes of previous studies (1,18). However, the amino acid variants in the P2 subdomain of these two strains did not cause any changes in the spatial conformation in our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study further analysed the VP1 protein, and the amino acid variation comparison revealed that it was greater in the P2 subdomain than in the P1 subdomain and S domain. Further, the threedimensional visualisation model of the VP1 protein also verified that there was a correlation between the alteration of the P2 subdomain and the alteration of the NoV genotype, which verified the outcomes of previous studies (1,18). However, the amino acid variants in the P2 subdomain of these two strains did not cause any changes in the spatial conformation in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Amino acid mutation of VP1. Mutations in the amino acids of the norovirus VP1 protein are important factors in the evolutionary mechanism of norovirus (18). Therefore, the amino acid sequences of the Bo/XJ-TC/01/CHN and Bo/XJ-KS/02/CHN VP1 proteins were compared with the VP1 proteins in the respective reference sequences with the highest amino acid homology: MN122335.1 and MZ573179.1.…”
Section: Epidemiological Survey Of Bnov In Xinjiangmentioning
confidence: 99%
“…16,17 For that reason, several genogroups and genotypes were categorised based on the VP1 sequence, including the prototypic GI.1 Norwalk strain, and novel emerging strains, such as the GII.17 Kawasaki strain responsible for recent outbreaks in Asia. 16,18,19 The general structure of VP1 is subdivided into two domains; the shell (S) domain, facing the inside of the capsid, and the protruding (P) domain, which is outward-facing and further divided into two subdomains, P1 and P2. 12,14,15 A comparison of the VP1 dimer of Norwalk and Kawasaki is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%